On zeros of functions analytic in a half plane and completeness of systems of exponents - Vynnyts’kyi, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Sequences of zeros are described for functions $f$ analytic in the right halfplanc and satisfying the condition $|f(z)| ≤ 0(1) \exp (σ|z|),\quad 0 ≤ σ ≤ ∞$ criterion of completeness of a system of exponentials in a space of functions analytic in a semistrip is established.